Utilization of Optical OFDM Modulation on Blue LED VLC Datacom Without Equalization for 4 m Wireless Link - Yuan-Zeng Lin; Chien-Hung Yeh; Wen-Piao Lin; Chi-Wai Chow (Micromachines)
To achieve higher visible light communication (VLC) traffic capacity, using the wide bandwidth light-emitting diode (LED) and spectral efficiency modulation signal, is currently the most commonly used method. In this demonstration, we apply the orthogonal frequency division multiplexing quadrature amplitude modulation (OFDM-QAM) with bit- and power-loading algorithm on single blue LED to achieve >1 Gbit/s VLC capacity, when a 400 MHz bandwidth avalanche photodiode (APD)-based receiver (Rx) is exploited for decoding. Here, the higher sensitivity APD can be applied to compensate for the wireless VLC link length in the proposed LED VLC system, and due to the lower LED illumination (255 to 40 lux), is used for the indoor access network after passing the wireless link length of 1 to 4 m. As a result, using single blue LED can achieve 0.962 to 1.057 Gbit/s OFDM rate with available 400 MHz bandwidth APD in poorly illuminated condition indoors without applying analogy equalization.